2014
DOI: 10.1097/dcr.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Resection With Pelvic Exenteration for Advanced Primary and Recurrent Pelvic Cancer

Abstract: This series supports sacral resection for curative surgery in advanced pelvic cancers, achieving excellent R0 and long-term survival rates. Cortical bone invasion and high sacrectomy were not contraindications to surgery and had acceptable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 28 publications
6
41
0
1
Order By: Relevance
“…Not only was positive resection margin a significant predictor of mortality, the present study showed overall survival was significantly poorer at 5 years after R1 or R2 resection. This is in keeping with previous findings. There was no significant difference in R0 resection rates between high versus low sacral resection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Not only was positive resection margin a significant predictor of mortality, the present study showed overall survival was significantly poorer at 5 years after R1 or R2 resection. This is in keeping with previous findings. There was no significant difference in R0 resection rates between high versus low sacral resection.…”
Section: Discussionsupporting
confidence: 92%
“…By using ultraradical exenterative techniques, long‐term survival can now be achieved in up to 60 per cent of patients with locally advanced and recurrent disease. Initially, involvement of the sacrum was considered a contraindication to curative exenteration; however, en bloc sacral excision to ensure clear resection margins is now performed routinely at specialist centres, with acceptable morbidity, oncological and functional outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Whether radical exenterative surgery is a treatment option partly depends on the level of sacral involvement. In most institutions, invasion above the S2-S3 junction is a relative contraindication to resection, although high sacrectomy is also practiced in some centers [92].…”
Section: Locoregional Recurrencementioning
confidence: 99%
“…С 1998 по 2012 г. они провели 79 подобных опе-раций. Согласно опубликованным данным, R0-резек-ция была достигнута в 72 % случаев [15]. Частота послеоперационных осложнений составила 74 %, об-щая 5-летняя выживаемость -38 %, безрецидивная -30 %, послеоперационной летальности не отмечено.…”
Section: анализ опубликованных исследованийunclassified